Review of Severity Rating Scales for Restless Legs Syndrome: Critique and Recommendations. Issue 4 (30th September 2014) - Walters, Arthur S.; Frauscher, Birgit; Allen, Richard; Benes, Heike; Chaudhuri, K. Ray; Garcia‐Borreguero, Diego; Lee, Hochang B.; Picchietti, Daniel L.; Trenkwalder, Claudia; Martinez‐Martin, Pablo; Schrag, Anette; Stebbins, Glenn
Abstract Over the last decade, research in restless legs syndrome (RLS; also known as Willis‐Ekbom disease) has increased dramatically. The International Parkinson and Movement Disorder Society commissioned a task force to formally evaluate the available evidence on severity rating scales in RLS. A literature search retrieved instruments specific to RLS. Each scale was evaluated by three criteria: (1) use in RLS; (2) use by research or clinical groups other than the group that developed the scale; and (3) formal validation and adequate clinimetric properties. Scales were then qualified as "recommended" when all three criteria were met, "suggested" when used for RLS but only one of the other criteria was met, and "listed" when only used in RLS. Details regarding the development, use, and psychometric properties of each instrument and the recommendations of the committee are summarized. The scale of the International Restless Legs Syndrome Study Group for rating the severity of RLS (International Restless Legs Scale or IRLS) and the Augmentation Severity Rating Scale fulfilled criteria for "recommended" instruments to assess severity. Future endeavors should include a validation of the Pediatric RLS Severity Scale, the only available instrument for evaluation of the severity of pediatric RLS, and a validation of a patient version of the IRLS that will not require the interface of a live interviewer.